Usefulness of a template‐based anterolateral thigh flap for reconstruction of head and neck defects. Issue 7 (21st August 2020) - Driessen, Caroline; van Hout, Naomi; van Kuppenveld, Phoebe; Cristobal, Lara; Liu, Tianyi; Mani, Maria; Rodriguez Lorenzo, Andres
Abstract: Background: One of the challenges in head and neck reconstruction is to have an adequate understanding of the three‐dimensionalities of the defects created after resections due to the high variability of clinical scenarios. Consequently, it is essential to design the flap to match the requirements of the defect in order to facilitate the insetting and to achieve a successful outcome. The anterolateral thigh flap (ALT) is a robust and versatile flap commonly used in head and neck reconstruction. In this study the authors use a hand‐made template as a tool to customize ALT flaps and its variations to fit more accurately the different shapes, volume, and components of the resulting defects. The aim of this study is to describe in detail this surgical approach and present the clinical experience in 100 consecutive cases using a template‐based ALT flaps in head and neck reconstruction. Methods: A retrospective review was performed on all microvascular head and neck reconstruction cases between January 2013 and December 2017 in our institution where a template‐based ALT flap design was performed. We describe in detail the surgical technique used and present the clinical outcomes. In addition, we analyzed the use of different designs of the ALT flaps including different flap components in relation to the location of the defect. Results: One hundred reconstructions for head and neck defects were performed in 97 patients. Seven types of ALT free flaps were performed: fasciocutaneous (46%), suprafascial (8%), adipofascial (9%), vastus lateralis muscle (3%), composite fasciocutaneous/adipofascial (9%), chimeric flaps (21%), and vascularized nerve grafts (4%). Oropharyngeal and periauricular defects were mostly reconstructed with fasciocutanoues design. In more complex three‐dimensional defects such as skull base or midface defects, a chimeric flap was selected. In all cases the used of template facilitated the insetting of the free flap. The total flap loss was 2%. Conclusions: Customization of ALT flaps using intraoperative templates is a useful method for flap design which facilitates fitting of the flap to a variety of defects in head and neck reconstruction.